A novel TRPS1 mutation in a Moroccan family with Tricho-rhino-phalangeal syndrome type III: case report - W. Smaili; S. Chafai Elalaoui; S. Meier; M. Zerkaoui; A. Sefiani; K. Heinimann (BMC, 2017)
Abstract Background Tricho-rhino-phalangeal syndrome (TRPS) is an autosomal dominant disorder characterized by craniofacial and skeletal malformations including short stature, thin scalp hair, sparse lateral eyebrows, pear-shaped nose and cone shaped epiphyses. This condition is caused by haploinsufficiency of the TRPS1 gene. Previous genotype-phenotype studies have correlated exon 6 missense mutations with TRPS type III, a severe form of type I with pronounced, facial characteristics, short stature and brachydactyly and differing from type II by the absence of exostoses and mental retardation. Case presentation We report the first case of a Moroccan family, a father and his three children, in which the diagnosis of type III TRPS was suspected based on severe clinical and radiological features. Molecular analysis of the TRPS1 gene revealed a novel missense mutation in exon 6, (p.Ala932Ser), located in the GATA-type DNA-binding zinc finger domain. Conclusion Our observations in this kindred support the previous genotype-phenotype results suggesting that patients with more pronounced facial characteristics and more severe shortening of hands and feet are more likely to have mutation in exon 6 of TRPS1.